2020
DOI: 10.1007/s00420-019-01513-5
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to noise and cold environment and the risk of death due to myocardial infarction and stroke

Abstract: Purpose The present study examined a possible association between occupational exposure to noise, working and living in cold conditions, and the risk of mortality in myocardial infarction and stroke. Methods The present cohort study consists of 194,501 workers in the Swedish construction industry that participated in health examinations between 1971 and 1993. Noise exposure was defined on a job-exposure matrix based on a survey of the working conditions carried out during the mid 1970s. All workers were catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 13 publications
3
34
0
Order By: Relevance
“…The magnitude of effect however, is dependent on noise intensity, duration, and type, as well as personal sensitivity 33 . Increased cardiovascular risks have also been noted for groups exposed to high levels of noise including mining, 35 trucking, 36 construction, 37 metal manufacturing, 38 and pulp and paper mills, 39 supporting important associations in our study. Workers should be educated about the harmful impacts of noise, and the use of hearing protection equipment to minimize potential workplace hazards.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The magnitude of effect however, is dependent on noise intensity, duration, and type, as well as personal sensitivity 33 . Increased cardiovascular risks have also been noted for groups exposed to high levels of noise including mining, 35 trucking, 36 construction, 37 metal manufacturing, 38 and pulp and paper mills, 39 supporting important associations in our study. Workers should be educated about the harmful impacts of noise, and the use of hearing protection equipment to minimize potential workplace hazards.…”
Section: Discussionsupporting
confidence: 82%
“…Radiation may also explain increased risks detected for uranium miners specifically, 41 and highlights the need for heightened CVD screening procedures in the workplace. Environmental stressors, such as cold temperature extremes, are occupational exposures for many outdoor, manual workers in our Canadian study as well 37 …”
Section: Discussionmentioning
confidence: 85%
“…For the 172 excluded studies that most closely resembled inclusion criteria, the reasons for exclusion are listed in Appendix 4 in the Supplementary data . After updating the search on January 31st 2020, one additional study, which met the inclusion criteria, was added to the list of included studies ( Pettersson et al, 2020 ). Of the 17 included studies in the systematic review, 14 were included in one or more quantitative meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Whenever needed, we attempted to contact the corresponding authors of respective publications and requested re-analysis of their data. This was done if the risk estimate was not reported in a suitable format for pooling together with other studies (e.g., a different cut-off exposure level; Pettersson et al (2020) ) or if multiple comparisons were reported within a study (e.g., a single control group and several exposed groups stratified by duration of exposure (e.g. Davies (2002) ) (see Appendix 2 in the Supplementary data ).…”
Section: Methodsmentioning
confidence: 99%
“…The noxious exposures aspect includes exposure to physical, chemical, and biological hazards, including climate and microclimate extremes. Workers exposed to noise, air pollution, and temperature extremes are at higher risk of developing arterial hypertension, dyslipidaemia, diabetes, coronary heart disease, and stroke ( 41 , 42 , 87 , 108 , 109 , 110 ).…”
Section: Discussionmentioning
confidence: 99%